Plan de negocio para la creación de una empresa de mantenimiento industrial en la parroquia de Patricia Pilar, provincia de los Ríos para el periodo 2015 - Alvario Mejía, Ruth Solanda (2015)
The business plan for the creation of a company of industrial maintenance in Patricia parish Pilar de Los Ríos province for 2015, it is executed with the aim of satisfying the need of the industrial sector in relation to the maintenance of the equipment and machinery; because of that the town is unavailable from industrial maintenance companies that provide this service, which has generated customer dissatisfaction. As a last instance proposed the design of the corporate image of the company, which consisted in developing the logo and isotype and indicate their respective name, allowing you the same recognized by customers within the industrial maintenance market; In addition considered the elaboration of marketing strategies, through the publication of ads on social networks, newspapers and radio, all of this in an effort to publicize the type of service provided by the company, and that at the same time place to compete within the industrial maintenance market. This paper consisted of a study of market through the implementation of surveys to managers of industrial enterprises, resulting in the need for creation of a company of industrial maintenance sector, followed by a technical study that determined the proper location of the project, as well as its size; subsequently executed the economic study that determined the investment required, which is $ 47.665,47, while the internal rate of return (IRR) was 54,35%, the net present value (range) of $ 66.809,73, and a relationship benefit cost (RBC) $1, 62; which indicates that the project is viable.